Harry Potter and Sorcerer's stone - Columbus, Chris; Heyman, David; Kloves, Stone; Heyday Films; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2002)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts School of Witchcraft and Wizardry
Based on the novel by J.K. Rowling
Title from title screen
Director of photography, John Seale ; production design, Stuart Craig ; editor, Richard Francis-Bruce ; music, John Williams
Casts: Daniel Radcliffe, Rupert Grint, Emma Watson, Richard Harris, Alan Rickman, Maggie Smith
In English, Mandarin and Cantonese with optional English, Chinese and Bahasa subtitles
Keywords: Rowling, J. K. -- Film and video adaptations; Wizards -- Drama; Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Drama; Fantasy films